Pengaruh Senam Dismenore Terhadap Penurunan Tingkat Nyeri Dismenore Remaja Putri Dd SMA Sanata Karya Langgur - Melania Wahyuningsih Wahyuningsih; Listyana Natalia R; Ona Enjela Letsoin (HEALTH CARE : JURNAL KESEHATAN, 2022)
Menstrual pain that occurs in middle adolescents can lead to decreased memory performance, inability to present assignments optimally, and absenteeism at school. Non-pharmacological pain management that can be done to treat dysmenorrhea can include dysmenorrhea exercise. This study aims to discover the effect of dysmenorrhea exercise in reducing the level of dysmenorrhea among adolescents at Sanata Karya Langgur Senior High School. This study is a quasi-experimental study with pre-test and post-test without control. The samples consist of 10 respondents are in the dysmenorrhea exercise group. The sampling technique is non probability sampling with the consecutive sampling method. The statistical analysis used before and after the dysmenorrhea exercise is the paired t test. The measuring instrument used is the numeric rating scale. The analyses of pain levels before and after the dysmenorrhea exercise obtained p=0.000 (<0.05). Dysmenorrhea exercise effective in reducing dysmenorrhea.